THE MEDIATING ROLE OF ENVIRONMENTAL KNOWLEDGE SHARING ON THE IMPACT OF GREEN LEADERSHIP ON INNOVATION IN VIETNAMESE SMALL AND MEDIUM ENTERPRISES - Bui, Thanh Khoa (Trường Đại học Đà Lạt, 2024)
With environmental sustainability gaining significance, firms require green leadership to drive the adoption of eco-innovations through appropriate culture-building. This quantitative study uses upper echelons theory to analyze green innovation levels in Vietnamese small and medium enterprises (SMEs) and to assess intermediary mechanisms that transmit strategic leaders’ influence. Results of partial least squares structural equation modeling (PLS-SEM) provide strong empirical support for the hypotheses that environmental knowledge sharing practices mediate the impact of green leadership behaviors on higher performance in green product and process innovation. Specifically, knowledge exchange through cross-functional collaborations and external partnerships explains the effect of leadership. Findings respond to calls for research on green innovation drivers in emerging markets such as Vietnam, where institutional pressures for ecological responsibility remain underdeveloped. Furthermore, identifying actionable transmission mechanisms informs policy guidelines regarding interventions necessary to nurture sustainable innovation. This study offers multi-level theoretical and practical contributions.